Role of Water in the Reaction Mechanism and endo/exo Selectivity of 1, 3‐Dipolar Cycloadditions Elucidated by Quantum Chemistry and Machine Learning. Issue 35 (24th May 2019) - Yang, Xin; Zou, Jun; Wang, Yifei; Xue, Ying; Yang, Shengyong
Abstract: Asymmetric 1, 3‐dipolar cycloadditions of azomethine ylides with activated olefins are among the most important and versatile methods for the synthesis of enantioenriched pyrroline and pyrrolidine derivatives. Despite both theoretical and practical importance, the role of water molecules in the reactivity and endo / exo selectivity remains unclear. To explore how water accelerates the reactions and improves the endo / exo selectivity of the cycloadditions of 1, 3‐dipole phthalazinium‐2‐dicyanomethanide (1 ) and two dipolarophiles, an ab initio‐quality neural network potential that overcomes the computational bottleneck of explicitly considering water molecules was used. It is demonstrated that not only the nature of both the dipolarophile and the 1, 3‐dipole, but also the solvent medium, can perturb or even alter the reaction mechanism. An extreme case was found for the reaction of 1, 3‐dipole 1 with methyl vinyl ketone, in which the reaction mechanism changes from a concerted to a stepwise mode on going from MeCN to H2 O as solvent, with formation of a zwitterionic intermediate that is a very shallow minimum on the energy surface. Thus, high stereocontrol can still be expected despite the stepwise nature of the mechanism. The results indicate that water can induce global polarization along the reaction coordinate and highlight the role of microsolvation effects and bulk‐phase effects in reproducing the experimentally observed aqueous acceleration and enhanced endo / exo selectivity. Abstract : Aqueous solvent effects : Quantum chemistry and neural network molecular dynamics simulations were used to interpret the experimentally observed acceleration and enhanced endo / exo selectivity of 1, 3‐cycloadditions of 1, 3‐dipole phthalazinium‐2‐dicyanomethanide with two dipolarophiles (methyl vinyl ketone and methyl acrylate) in the presence of water (see figure).